Including Organizational Ethics in the Risk Management Process: Towards Improved Practices and Analysis - Bouchard, Laurie; Dion-Labrie, Marianne (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
Risk management has played an important role in Quebec’s health and social services organizations for several years. This process is based on two guiding principles: the just culture and the no-blame concept and is an integral part of the Act respecting healthcare and social services. However, for all its usefulness, the current risk management process has certain limitations and criticisms. To overcome these weaknesses, the association of organizational ethics with the risk management process represents an interesting option. The use of organizational ethics concepts and tools overcomes the limitations of risk management and even optimizes it. Both are organizational processes with many common objectives and links, and both provide tools for decision-making. The combination of organizational ethics and risk management broadens the scope of risk management. To enable the best possible optimization, an analysis grid is proposed, and recommendations are made for the inclusion of ethics in risk management.